2001
DOI: 10.1073/pnas.131087598
|View full text |Cite
|
Sign up to set email alerts
|

Submucosal gland secretions in airways from cystic fibrosis patients have normal [Na+] and pH but elevated viscosity

Abstract: ASL ͉ chloride ͉ trachea ͉ ratio imaging T he air-facing surface of respiratory airways is lined by a layer of surface epithelial cells whose mucosa is bathed by a thin film of fluid called the airway surface liquid (ASL) (1-5). The airways also contain submucosal glands that secrete fluid and macromolecules onto the ASL (6-9). The submucosal glands contain serous tubules and acini that secrete salt, water, and various antimicrobial proteins. The serous secretions pass through mucous tubules, where viscous gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
177
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(197 citation statements)
references
References 42 publications
16
177
4
Order By: Relevance
“…Our observations also appear to conflict with ex vivo studies of CF gland preparations that have shown decreased agonist-stimulated glandular secretion rates and a more viscous (increased mucin concentration) secretion, implying that CFTR is involved in regulating glandular fluid volume (Jayaraman et al, 2001;Joo et al, 2002). However, in every functional ex vivo study of normal and CF tissues, all the glandular components (e.g., acini and ducts) and adjacent gland tissue/cells (e.g., muscle cells) were exposed to the pharmacological stimulus, and glandular secretions were analyzed at the duct entrance onto the airway surface (Joo et al, 2002;Verkman et al, 2003;Ballard and Inglis, 2004).…”
Section: Function Of Glands In Airway Fluid Balancecontrasting
confidence: 89%
“…Our observations also appear to conflict with ex vivo studies of CF gland preparations that have shown decreased agonist-stimulated glandular secretion rates and a more viscous (increased mucin concentration) secretion, implying that CFTR is involved in regulating glandular fluid volume (Jayaraman et al, 2001;Joo et al, 2002). However, in every functional ex vivo study of normal and CF tissues, all the glandular components (e.g., acini and ducts) and adjacent gland tissue/cells (e.g., muscle cells) were exposed to the pharmacological stimulus, and glandular secretions were analyzed at the duct entrance onto the airway surface (Joo et al, 2002;Verkman et al, 2003;Ballard and Inglis, 2004).…”
Section: Function Of Glands In Airway Fluid Balancecontrasting
confidence: 89%
“…Similarly, elevated NaCl concentrations have been reported in CF airway fluids (19). However, it has then been shown that airway-surface liquid in CFTR-null mice is approximately isotonic (20) and that submucosal gland secretions in airways from patients with CF have normal [Na + ], although presenting elevated viscosity (21). Contrary to α7 nAChR, absence of either α5, β2, or β4 nAChR subunit does not impact on airway mucus transport in mice (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…It has been reported that CF-affected epithelia, particularly in the gastrointestinal tract, secrete fluid with a more acidic pH than normal epithelia (11,12). Whether this is also true for airway surface liquid is still controversial (13,14), but recent measurements of the pH and HCO 3 Ϫ concentration of fluid secreted by polarized human submucosal gland cells, Calu-3, indicate that these cells are capable of secreting substantial amounts of HCO 3 Ϫ (ϳ80 mM) under appropriate stimulation, a process that would be defective in CF (15). An acidic luminal environment affects the physical properties of mucus (16,17) and promotes bacterial binding to mucins (18,19), both of which may have important implications for CF lung disease (20).…”
mentioning
confidence: 99%